Optimal design of a novel modified electric eel foraging optimization (MEEFO) based super twisting sliding mode controller for controlling the speed of a switched reluctance motor - Debiprasanna Das; Binod Kumar Sahu; Swagat Pati; Bhabasis Mohapatra; Debashis Sitikantha; Mohit Bajaj; Vojtech Blazek; Lukas Prokop (Scientific Reports)
Abstract Switched Reluctance Motor (SRM) has a very high potential for adjustable speed drive operation due to their cost-effectiveness, high efficiency, robustness, simplicity, etc. Now a days SRMs are widely used in automotive industries as traction motors in electric vehicles and hybrid electric vehicles, air-conditioning compressors, and for other auxiliary services. In this article, a novel super twisting sliding mode controller (STSMC) is proposed to improve the performance of an SRM for reducing the ripple in speed and torque. Initially, a novel Modified Electric Eel Foraging Optimization (MEEFO) technique is developed by incorporating a quasi-oppositional phase and its performance is compared with the conventional Electric Eel Foraging Optimization (EEFO) technique with four popular benchmark functions. Then, both MEEFO and EEFO techniques are implemented to optimally design PI, SMC and STSMC controllers to effectively control the speed of an SRM. The study is carried in three different scenarios such as during starting, during a torque change and during a speed change. Finally, performance of the SRM in real time is studied with OPAL-RT 4510 simulator. It is observed that MEEFO based STSMC exhibits significant improvements in effectively controlling speed of the SRM, as compared to its other proposed counterparts.